Molecular Identification and Antibacterial Activity of Streptomyces spp. Isolated from Sulaymaniyah Governorate Soil, Iraqi Kurdistan - Syamand A. Qadir; Osama H. Shareef; Othman A. Mohammed (Polytechnic Journal)
Soil is play an important role for reserve abundant groups of microorganisms, especially Streptomyces. Streptomyces are recognized as prokaryotes, aerobic and Gram-positive bacteria with high Guanine + Cytosine contents in their DNA. These groups of bacteria show filamentous growth from a single spore and they are normally found in all kinds of ecosystems, including water, soil, and plants. A total of three Streptomyces strains were isolated from soil of the sides of Darband Ranya in Sulaimani governorate. Different approaches were followed for the identification of the isolated stains. Morphological and cultural properties of these isolates have shown that the isolates are belonging to the genus Streptomyces. Desired colonies of the isolates were distinguished and separated from other bacteria on the basis of colony morphology, pigmentation, ability to produce a different color of aerial hyphae, and bottom mycelium on raffinose-histidine agar and starch-casein agar media. In addition, analysis of phylogenetic tree based on 16S rRNA gene sequences, the strains related the genus. KS010 isolates had the highest identity (99.32%) with the type strain of Streptomyces atrovirens, while KS005 and KS007 isolates were most closely related to Streptomyces lateritius by identity 99.32%. The isolated test strains were also active against Gram-negative and Gram-positive pathogenic bacteria following co-cultivation technique. However, further study should be done to identify the types of these antibacterial compounds.